LEGAL ANALYSIS OF THE PUBLIC PROSECUTOR'S CONSIDERATIONS TO DETERMINE THE SEVERITY OF THE CLAIMS AGAINST THE DEFENDANT IN NARCOTICS CRIME (STUDYING AT THE PROSECUTOR'S PROSECUTION IS REALLY FUN) - Syam, Ismail; Sahari, Alpi; Zulyadi, Rizkan (NOMOI Law Review, 2023)
Prosecution to something follow criminal narcotics is functions carried out by the Prosecutor's Office , in matter This prosecutor general . In letter demands mentioned , are included consideration in submit demands the punishment consists of from aggravating things and mitigating things _ _ defendant . In determine heavy its light demands in case follow criminal narcotics , then prosecutor Prosecutor General in general _ refers to regulation legislation . Study This use study law normative . In study law normative research _ more emphasize study of principles law and synchronization law to regulation governing legislation. Rule governing law _ about heavy it's light demands made _ prosecutor Prosecutor General in Act Criminal Narcotics arranged in the Guidelines Number 24 of 2021 Concerning Handling Case Act Criminal General and Guidelines Number 11 of 2021 concerning Handling Case Act Criminal Narcotics and/ or Act Criminal Precursor Narcotics , no only That in Law no. 35 of 2009 concerning Narcotics also regulate about its weight sanctions imposed _ based on group . Procedure giving demands For determine heavy its light criminal as material consideration prosecutor Prosecutor General to case follow criminal narcotics started from listen information witnesses and defendants added information expert at trial.